High downforce race car vertical dynamics: aerodynamic index. Issue 8 (3rd August 2018) - Marchesin, Felipe Pereira; Barbosa, Roberto Spinola; Gadola, Marco; Chindamo, Daniel
ABSTRACT: Race car performance is strongly affected by aerodynamics. Due to downforce generated by the vehicle floor (i.e. diffuser), vehicle ride heights are key parameters to improve performance, and the coupling of aerodynamics and suspension is one of the key points of race car setting. This work focuses on the suspension and aerodynamic coupling from the vertical dynamics point of view. Besides road holding performance, for race cars, aerodynamic performance and stability are major factors. Downforce decreases laptime (the main performance target) but pitch instability is a non-desired effect that can happen in high downforce race cars. A new vertical dynamic performance index is proposed through the use of simulation to improve aerodynamic performance and understand the pitch instability phenomenon. This new index uses all relevant vehicle nonlinearities related to vertical dynamics and can handle a specific track profile and vehicle speed range, allowing the analysis be conducted according to a circuit specification. A previously validated Formula 3 car model was used as an example.